The Power Usage of School Administrators in Kamphaengsean District under Nakhonprathom Educational Service Area Office 1 - Thaweechoknimit, Chalida; Parunggul, Chuan (Journal of Innovation and Management, 2020)
The purposes of this research were to (1) study the power usage of administrators in Kamphaengsean district under Nakhonprathom Educational Service Area Office 1 and (2) to make a comparison of the power usage of administrators in Kamphaengsean district under Nakhonprathom Educational Service Area Office 1 by school groups. By quantitative research methods. The samples group consisted of 246 teachers. The instruments used for collecting data were 5 rating scales questionnaires with reliability . 96. The statistics used for data analysis were frequency, percentage, arithmetic means, standard deviation and F- test ( One Way ANOVA) . The research results were as follows: (1) The power usage of the administrators in Kamphaengsean district under Nakhonprathom Educational Service Area Office 1 as a whole was at a high level. Considering the features of each aspect, were found have at the highest level in 1 aspect and in the high level of 6 aspects as follows; Information Power, Referent Power, Expert Power, Legitimate Power, Reward Power, Ecological Power and Coercive Power, and ( 2) the comparison of the power usage of the administrators in Kamphaengsean district under Nakhonprathom Educational Service Area Office 1 by school groups does not show very significantly differences at the .05 level. Considering the features of each aspect, were found have Referent Power and Expert Power are significantly different at the . 05 level, other than that no difference.